Merdeka Belajar di Tengah Pandemi COVID-19: Studi di Sekolah Menengah Pertama di Indonesia - Mardiana, Dina; Umiarso, Umiarso (Institut Agama Islam Negeri Kendari, 2020)
The COVID-19 pandemic has a major influence on Indonesia's education system. The enactment of Merdeka Belajar or freedom to learn as the Ministry of Education and Culture of the Republic of Indonesia's regulation is quickly gaining ground due to this pandemic. This paper presents the results of an investigation into the educational trend at an Indonesian high school during the mid-COVID-19 crisis. In this case study, online semi-structured interviews were used. The results indicate that during the COVID-19 pandemic the Merdeka Belajar strategy has been enacted by improving the technological training mechanism available to schools. The first step is to develop the school's internal curriculum through Kampus Merdeka policy and introduce COVID 19 prevention protocols in schools. The second strategy is empowering web-based teaching integration and online asynchronous education.